Analysis of The Implementation of The Early Child Growth and Nutrition Detection Program Based on PAUD at The Leppangan Public Health Center - Sastri; Melisyah; Jumriani; Sri Istiana Marsuki; Maswati; Eka Sapira; Rezki; Nurul Izza (CV Edujavare Publishing, 2026)
The early detection program for growth and nutrition in early childhood is a strategic effort in preventing nutritional problems, particularly stunting. This study aims to analyze the implementation of the PAUD-based early detection program for growth and nutrition in Leppangan Community Health Center. This study used a qualitative descriptive approach with data collection techniques through in-depth interviews with health workers and documentation of child growth and development monitoring results. The results showed that the program has been implemented through integrated health service posts (Posyandu), visits to PAUD, and community health center services using standard anthropometric indicators (weight/age, height/age, weight/height, BMI/age). The monitoring results showed that the majority of children were in the well-nourished category, but cases of malnutrition and stunting were still found. The main obstacles include limited resources and family economic factors. Efforts made include education, providing supplementary food, home visits, and strengthening the role of Posyandu cadres. This study concluded that the program has been running structurally, but not optimally functionally, so that strengthening cross-sector collaboration and a family-based approach is needed.